Touching through the screen: embodied learning through on-line intercultural exchanges among primary school children. Issue 6 (7th September 2022) - Walton, Jessica
Abstract: This paper is based on ethnographic research of Australian and South Korean primary school students' experiences of on-line synchronous intercultural exchanges as part of a school partnership. Starting with an embodied understanding of learning, I discuss the applicability of body pedagogies to the on-line context in a classroom setting by analysing how the institutional dimension ('situated epistemic relations') informed how the children were taught to engage during on-line intercultural exchanges in relation to the children's embodied experiences of the exchanges ('practical epistemological analysis'). Through a more holistic approach that includes the body as integral to the students' digitally-mediated interactions, this paper provides a deeper understanding of the students' intercultural learning that is not limited to a cognitive focus on language learning and skill acquisition. I conclude with thoughts on future research directions including how children's embodied experiences of intercultural exchanges may contribute to the longer-term development of an 'intercultural habitus'.